pre cal

posted by .

(y^2)^-4y^8 simplify

• pre cal -

y^2 - 4y^8 = y^2 - (2y^4)^2
= (y + 2y^4)(y - 2y^4)

formulas a^2 - b^2 = (a + b)(a - b)

• pre cal -

Or, seeing that the expression as written is meaningless, and assuming the usual carelessness with parentheses,

(y^2)^(-4) * y^8
= y^(2 * -4) * y^8
= y^(-8) * y^8
= y^(-8+8)
= y^0
= 1

Similar Questions

1. PRE-CAL

SIMPLIFY 55/SQUARE ROOT OF 20 -3
2. pre-cal

can anyone please explain to me how to simplify this exponential expression?
3. Pre-Cal

Simplify e^3ln2-1
4. Pre Cal

simplify the expression 2sin^2 t + cos^2 t-2
5. Pre Cal

simplify the quotient: [x(5x+1)-3(x^2+1)]/ [(x-1)^2]
6. Pre Cal

simplify the quotient: [(x+1)^3(4x-9)-(16x+9)(x+1)^2]/[(x-6)(x+1)^3]
7. Pre-Cal

For given functions f and g find formulas for a)f o g and b)g o f. Simplify results as much as possible. f(t)= t-3/t+6 , g(t)= 1/(x+6)^2
8. Pre-cal

Simplify: A) log(x+1)+3logx B) 2log4np-3log4p C) 2ln(3x)+ln(5x)-ln6xy D) 22log10+log1000-log1
9. Pre-Cal

Confirm that f and g are inverses by showing that f(g(x)) = x and g(f(x)) = x. f(x) = (x-7)/(x+3) and g(x) = (-3x-7)/(x-1) I got to the point where f(g(x)) is plugged in but how would I simplify it?
10. pre cal

Can you simplify (2x^-4 y^-1 times 2y^4 z^-1)^-2/ 2yx^3 z^0 I got the numerator to be 16x^16 y^17 z and then divided by the denominator to get 8x^13y^16z

More Similar Questions